Improvement in tribological properties of lubricating grease with quartz-enriched rice husk ash. (January 2016) - Akhtar, Khalida; Khalid, Hina; Ul Haq, Ikram; Malik, Abdul
Abstract: This study deals with the isolation of quartz-enriched ash from the rice husk by heating at 450 °C and subsequent treatment with an acid solution. It was characterized by scanning electron microscopy, X-ray diffracometry and energy-dispersive X-ray analysis. Various amounts of this ash were mixed with commercial lithium based grease at room temperature and tested for their antiwear performance. Four ball tribometer was used as a wear tester. Results revealed that the mentioned additive improved the performance of grease to a significant extent. The optimum amount of the dispersed ash was established in which the composite grease showed highest antiwear performance. In all cases, the performance of the composite grease was found better than the plain grease under the given test conditions. Highlights: Heating at 450 °C in air transformed rice husk into gray color rice husk ash (RHA). RHA was identified as a source of quartz, cristobalite and moganite. Cristobalite and moganite were acid soluble whereas quartz was not. Mixing of quart-enriched RHA in the Li-based grease improved its antiwear properties.